2006
DOI: 10.1159/000094717
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Photocatalytic Agent on DS-<i>Nh</i> Mice, Developing Atopic Dermatitis-Like Eruption with an Increase of <i>Staphylococcus aureus</i>

Abstract: Background:Staphylococcus aureus(S. aureus) is thought to play a significant role in the exacerbation of atopic dermatitis (AD). DS-Nh mice, a non-hair-bearing mouse model of AD, spontaneously develop dermatitis under conventional conditions. A remarkable increase in S. aureus is considered to strongly relate to the induction and aggravation of this dermatitis. A topical use of anatase-type titanium dioxide (TiO2) followed by UV irradiation, acting as photocatalyst, is believed to have antibacterial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 45 publications
0
8
0
Order By: Relevance
“…For example, a sub-erythemal dose ultraviolet radiation exposure (UVB 270 mJ/cm 2 ) in mice has been shown to allow the penetration of 45 nm quantum dot NPs to deep dermis [27]. In another study, it has been observed that 7 nm TiO 2 NP exposure with UV irradiation can lead to increased skin barrier dysfunction and possible aggravation of contact dermatitis due to increased invasion of Staphylococcus aureus [28]. Interestingly, people tend to apply more sun screens containing NPs in case they have damaged skin (sunburns, burns) when the barrier function of skin is already impaired.…”
Section: Discussionmentioning
confidence: 99%
“…For example, a sub-erythemal dose ultraviolet radiation exposure (UVB 270 mJ/cm 2 ) in mice has been shown to allow the penetration of 45 nm quantum dot NPs to deep dermis [27]. In another study, it has been observed that 7 nm TiO 2 NP exposure with UV irradiation can lead to increased skin barrier dysfunction and possible aggravation of contact dermatitis due to increased invasion of Staphylococcus aureus [28]. Interestingly, people tend to apply more sun screens containing NPs in case they have damaged skin (sunburns, burns) when the barrier function of skin is already impaired.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, once TiO 2 nanoparticles penetrate into the skin, they can affect the cutaneous function. Kambara et al reported that anatasetyped TiO 2 nanoparticles can accelerate skin barrier dysfunction/defect induced by UV irradiation in mice (32). Additionally, fluoresceinated quantum dots following intradermal injection (15-20 nm) have been shown to migrate to local lymph nodes in mice and pigs (43).…”
Section: Discussionmentioning
confidence: 99%
“…Then the plates were incubated at 37°C for 24 hrs. After incubation, the number of colonies was counted and identification of the bacteria was done according to the manufacturer’s instructions (20). Serum samples for SEB-specific IgE were measured using ELISA Plates coated with SEB (1 μg/ml, Toxin Technology, Inc.) in 0.1 M carbonate-bicarbonate buffer (pH 9.5) overnight at 4°C, as described previously (21).…”
Section: Methodsmentioning
confidence: 99%